Superoxide Dismutase Mimics: Chemistry, Pharmacology, and Therapeutic Potential - Batinić-Haberle, Ines (Mary Ann Liebert, Inc., 2010)
Oxidative stress has become widely viewed as an underlying condition in a number of diseases, such as ischemia–reperfusion disorders, central nervous system disorders, cardiovascular conditions, cancer, and diabetes. Thus, natural and synthetic antioxidants have been actively sought. Superoxide dismutase is a first line of defense against oxidative stress under physiological and pathological conditions. Therefore, the development of therapeutics aimed at mimicking superoxide dismutase was a natural maneuver. Metalloporphyrins, as well as Mn cyclic polyamines, Mn salen derivatives and nitroxides were all originally developed as SOD mimics. The same thermodynamic and electrostatic properties that make them potent SOD mimics may allow them to reduce other reactive species such as peroxynitrite, peroxynitrite-derived CO(3)(·−), peroxyl radical, and less efficiently H(2)O(2). By doing so SOD mimics can decrease both primary and secondary oxidative events, the latter arising from the inhibition of cellular transcriptional activity. To better judge the therapeutic potential and the advantage of one over the other type of compound, comparative studies of different classes of drugs in the same cellular and/or animal models are needed. We here provide a comprehensive overview of the chemical properties and some in vivo effects observed with various classes of compounds with a special emphasis on porphyrin-based compounds. Antioxid. Redox Signal. 13, 877–918.